One-pot synthesis of calcium-incorporated MCM-41 as a solid base catalyst for transesterification of palm olein - Jonggol Tantirungrotechai (2018)
Direct generation of basic sites on mesoporous silica MCM-41 through calcium incorporation was achieved via a one-pot synthesis. The effect of calcium salt precursors was addressed in terms of structure, morphology, and basic property. The catalysts were evaluated for potential application in transesterification of palm olein with methanol to produce biodiesel. Among all of the catalysts tested in this study, the most efficient calcium-incorporated MCM-41 was derived from CaO precursor, affording over 90 wt.% of fatty acid methyl ester after 3 h of reaction at 200°C. © 2011 Elsevier B.V. All rights reserved.